2022
DOI: 10.1101/2022.05.09.491201
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 mRNA third dose induces a unique hybrid immunity-like antibody response

Abstract: The continuous evolution of SARS-CoV-2 generated highly mutated variants, like omicron BA.1 and BA.2, able to escape natural and vaccine-induced primary immunity1,2. The administration of a third dose of mRNA vaccines induces a secondary response with increased protection. We investigated, at single-cell level, the longitudinal evolution of the neutralizing antibody response in four donors after three mRNA doses3. A total of 4,100 spike protein specific memory B cells were single cell sorted and 350 neutralizi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(32 citation statements)
references
References 33 publications
2
30
0
Order By: Relevance
“…Human samples from COVID-19 infected and vaccinated donors, who received two or three vaccine doses, of both sexes, who gave their written consent, were previously collected through a collaboration with the Azienda Ospedaliera Universitaria Senese, Siena (IT) 16,17 . Subjects in the seropositive 2 nd dose cohort resulted positive to SARS-CoV-2 infection between October and November 2020 16 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Human samples from COVID-19 infected and vaccinated donors, who received two or three vaccine doses, of both sexes, who gave their written consent, were previously collected through a collaboration with the Azienda Ospedaliera Universitaria Senese, Siena (IT) 16,17 . Subjects in the seropositive 2 nd dose cohort resulted positive to SARS-CoV-2 infection between October and November 2020 16 .…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the functional characterization and epitope mapping analyses, we investigated the B cell germline and V-J gene rearrangements (IGHV;IGHJ) used by highly cross-reactive nAbs against omicron variants. Of the 482 nAbs assessed in this study we previously recovered 430 heavy chain sequences: 46 from SN2, 176 from SN3 and 208 from SP2 16,17 . In SN2 subjects, predominant B cell germlines neutralizing the Wuhan strain include IGHV1-69;IGHJ4-1, IGHV3-30;IGHJ6-1, IGHV3-53;IGHJ6-1, IGHV3-66;IGHJ4-1 B cell germlines 16,[22][23][24][25] .…”
Section: B Cell Germline Usage Of Cross-neutralizing Omicron Nabsmentioning
confidence: 99%
See 2 more Smart Citations
“…As the immune system processes the same antigen in different forms there are numerous opportunities for processing the protein in different manners that can diversity the specificity of the immune response and thus increase the likelihood of eliciting antibodies that react with variant proteins. Stucturally, it has been shown that mRNA third dose vaccination induces mostly mainly class 1/2 antibodies encoded by IGHV1-58;IGHJ3-1 and IGHV1-69;IGHJ4-1 germlines, but not the IGHV2-5;IGHJ3-1 germline, broadly cross-reactive Class 3 antibodies seen after infection 39 .…”
Section: Discussionmentioning
confidence: 99%